MESSAGE FROM THE DEAN OF GRADUATE SCHOOL ASSUMPTION UNIVERSITY - Phothikitti, Kitti (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
It is indeed a great privilege for the Graduate School of Business, Assumption University, to host the International Conference on Entrepreneurship and Sustainability in the Digital Era (ICESDE). The conference marks not only an important milestone of Assumption University, but also a significant event on which selective papers from both domestic institutes and international institutes would be presented and discussed. Such works reflect great efforts, endurance and integration of comprehensive perspectives. We wish to extend our appreciation and our heartfelt thanks go to the scholars, professors, experts, and faculty members for their insightful selection of the research papers and for their suggestions. The Graduate School of Business owes it a great deal to the kindness, generosity, and guidance of the Executives of Assumption University, Deans and Directors of all schools concerned with the making of the conferences. A big thank is offered to all sub-committee members and the staff for their contribution and tireless assistance to have made this event possible. As an interdisciplinary forum, the conference brings together scholars, practitioners, and graduate students from the region and beyond to discuss their research findings on how environmentalfriendly and socially-inclusive growth and success can be sustained in the digital era, in Thailand in particular as it recently embarked on Industry 4.0. Keynote and feature speakers will provide a variety of perspectives on the conference themes. I strongly wish that such creation of new knowledge at this forum— be it from the papers being presented or from the exchange and discussion over the presentations—would produce the added values on our mutual quest for knowledge, thereby benefiting our respective communities and countries.